Comparison between the 10- and the 30-s-long Wingate Anaerobic Test in summer Paralympic athletes with a lower limb impairment - Cavedon, V.; Rosponi, A.; Alviti, F.; De Angelis, M.; Guerra, E.; Rodio, A.; Di Giacinto, B.; Milanese, C.; Bernardi, M. (Sport Sciences for Health, 2021)
Background: The 30-s-long Wingate Anaerobic Test (WAnT_30s) has some limitations in high-level athletes. A shorter ver-sion might be helpful for both clinical applications and performance assessment. The comparison between the traditional WAnT_30s and a shorter version has never been carried out yet in Paralympic athletes. Aim: To assess if a 10-s-long Wingate Anaerobic Test (WAnT_10s) could be used to accurately assess and predict the anaero-bic components of physical fitness as an alternative to the traditional WAnT_30s in male Paralympic athletes. Methods: Forty-four trained male Paralympic Athletes grouped by severity of locomotor impairment completed the WAnT_30s and the WAnT_10s with an arm cranking ergometer. Differences between mean and peak power achieved throughout both WAnTs were analysed using a mixed-design analysis of variance and predictivity was assessed by stepwise linear regression analysis. Results: In the whole sample, peak power values were similar (P > 0.005) in the two tests and the WAnT_10s mean power was significantly higher than that in the WAnT_30s (P < 0.005). Finally, the mean power measured during WAnT_30s showed high level of predictability from mean power measured during WAnT_10s and the Functional class (adjusted R2 = 0.906; P < 0.001). Conclusion: The WAnT_10s is accurate to assess peak power, is definitively appropriate to evaluate the alactic anaerobic metabolism and seems able to predict the mean power as traditionally evaluated through a WAnT_30s in male Paralympic Athletes. Thus, it can be used to assess the anaerobic components of physical fitness in this athletic population.